Sistem Penjualan Online Berbasis Website (Studi Kasus di Infomedia Komputer) - Tekat Budi Santoso; Edy Susena (LPPM Politeknik Jambi, 2019)
Infomedia Computer is a company engaged in the sale of computers and devices related to computers. Use of the right sales method is very important so that the company can continue to compete with other companies. In this case Surakarta Computer Infomedia still uses direct sales method where sales transactions are carried out in the store. This is considered to be no longer relevant in this modern era, which has all been integrated with the internet. Therefore, it is necessary to improve the system or method of buying and selling transactions. To create an online sales system to increase sales at Surakarta Computer Infomedia in order to continue to compete with other companies. Making this system is based on website programming. The method of data collection uses the method of observation, interviews and literature. Tools used to design systems are Flowcharts, Context Diagrams, DFD (Data Flow Diagrams), and ERD. The results of the implementation of the program that has been made is an e-commerce website which has helped promote the products sold by Surakarta Computer Infomedia. Easy management and operation by admin and customers because the system implements a friendly user system. The system can also be accessed with any device and has a responsive appearanc.